ความพึงพอใจของผู้รับบริการต่อการบริการส่งเสริมสุขภาพของเภสัชกรในร้านยา เขตกรุงเทพมหานคร CLIENTS’ SATISFACTION WITH HEALTH PROMOTION SERVICES PROVIDED BY COMMUNITY PHARMACISTS IN BANGKOK - ฉลองสุข ระพีพรรณ; อารีย์ วัฒนา (Thai Bulletin of Pharmaceutical Sciences, 2016)
ร้านยา 87 แห่งในกรุงเทพมหานครได้เข้าร่วมโครงการบริการงานส่งเสริมสุขภาพในร้านยาของสมาคมเภสัชกรรมชุมชน (ประเทศไทย) ทั้งนี้โครงการนี้ให้บริการโดยไม่คิดค่าใช้จ่ายกับผู้มารับบริการ โครงการนี้มีการส่งเสริมสุขภาพและป้องกันโรคทั้งหมด 12 กิจกรรม ได้แก่ การคัดกรองความเสี่ยงในกลุ่มภาวะโรคเมตาบอลิก (F01) การให้ความรู้เรื่อง ภาวะเมแทบอลิกซินโดรม ครั้งที่ 1 (F02) การให้ความรู้เรื่อง ภาวะเมแทบอลิกซินโดรม ครั้งที่ 2 (F03) การให้ความรู้เรื่องวัคซีนในเด็กอายุ 0-14 ปี (EPI Program) (F04) การให้ความรู้และป้องกันการเป็นโรคเรื้อรังที่เกี่ยวกับระบบทางเดินหายใจ (F05) การให้ความรู้และป้องกันโรคโดยการฝากครรภ์ (F06) การให้ความรู้เรื่องยาคุมกำเนิด ชนิดรับประทาน (F07) การให้ความรู้เรื่องยาคุมฉุกเฉิน (F08) การให้ความรู้เรื่องการใช้ถุงยางอนามัย (F09) การให้ความรู้เรื่องโรคที่เกิดจากการมีเพศสัมพันธ์ และ Pre-VCT (F10) การให้ความรู้เรื่องการตรวจคัดกรองมะเร็งปากมดลูกโดยวิธี Pap Smear (F11) การติดตามผล Pap Smear (F11-1) การให้ความรู้ คำแนะนำและคำปรึกษากรณีท้องไม่พร้อม (F12) วัตถุประสงค์ของการศึกษาคือ การสำรวจความพึงพอใจของผู้ที่ได้รับบริการที่ร้านยา โดยการสุ่มผู้รับบริการ 404 คนจากฐานข้อมูลบันทึกการให้บริการทั้งหมดของโครงการและสัมภาษณ์ทางโทรศัพท์ในช่วงวันที่ 26 มิถุนายน 2557 ถึงวันที่ 19 กรกฎาคม 2557 ผลการศึกษาพบว่าผู้รับบริการมีความพึงพอใจในบริการที่ได้รับทุกกิจกรรม โดยมีคะแนนความพึงพอใจเฉลี่ย 9.2±0.9 คะแนนจากคะแนนเต็ม 10 คะแนน โดยเฉพาะบริการ F09 และ F10 ผู้รับบริการร้อยละ 0.2 กลับมาใช้บริการอื่น ๆ เพิ่มเติม และร้อยละ 60.4 ได้แนะนำให้คนอื่นไปใช้บริการของโครงการนี้ ในการให้บริการส่งเสริมสุขภาพในร้านยานี้ต้องให้บริการในเวลาที่รวดเร็ว ดังนั้นเภสัชกรจึงต้องมีทักษะในการสื่อสารที่มีประสิทธิภาพเพื่อให้คำปรึกษาที่ชัดเจน กล่าวโดยสรุป เภสัชกรชุมชนสามารถให้บริการส่งเสริมสุขภาพแก่ผู้ที่มารับบริการที่ร้านยาได้ Eighty seven community pharmacies in Bangkok had participated the charge-free health promotion program of the Community Pharmacy Association (Thailand). There were 12 activities of health promotion and disease prevention including screening for metabolic syndrome (F01), providing counseling about metabolic syndrome (F02, F03), providing information of the Expanded Program on Immunization (EPI) (F04), providing health education about chronic respiratory disease (F05), counseling of pre-natal (F06), counseling of contraceptive pill (F07), counseling of emergency contraceptive drug (F08), counseling of condom use (F09), counseling of Sexually Transmitted Infections and Pre-Voluntary Testing (F10), counseling of Pap Smear (F11), Pap Smear test follow-up (F11-1) and counseling of family planning, safe sex and unwanted pregnancy (F12). The aim of this study was to evaluate clients’ satisfaction with health promotion services provided by community pharmacists. The 404 clients, randomized from service database of the program, were interviewed by telephone about their satisfaction of health promotion service. The interview was conducted between June 26 and July 19 2014. The results show that clients were satisfied with all activities of the health promotion service provided by community pharmacists. The average score of their satisfaction (10 rating scale) was 9.2±0.9 scores, especially for F09- and F10-service. Some of participants (0.2%) had come back to use another service and 60.4% of them had recommend these activities to others. There was a short time for each service of health promotion service in the community pharmacy. Since quick service time must be implemented, pharmacist should have effective communication skills to provide clear counseling result. In conclusion, community pharmacist can provide health promotion to clients visiting community pharmacies.